Sensitivity to change of oral and general health‐related quality of life during prosthodontic treatment. (6th December 2013) - Wickert, Melanie; John, Mike T.; Schierz, Oliver; Hirsch, Christian; Aarabi, Ghazal; Reissmann, Daniel R.
<x xml:space="preserve">Abstract</x> The literature presents conflicting findings on whether health‐related quality of life (HRQoL) measures have sufficient evaluative properties to assess changes caused by dental interventions. The aim of our study was to compare sensitivity to change in HRQoL and OHRQoL in prosthodontic patients. In this prospective intervention study, a total of 165 consecutively recruited patients completed the Short Form‐36 (SF‐36) and the 49‐item Oral Health Impact Profile (OHIP), as self‐administered questionnaires, before prosthodontic treatment and 1 month after treatment was finished. Differences in SF‐36 and OHIP scores between baseline and follow up were tested for statistical significance using paired t‐tests. Effect sizes (Cohen's d) were calculated. Health‐related quality of life improved during prosthodontic treatment, indicated by a slight, but statistically significant, increase in the SF‐36 physical component (difference: 1.0 points), whereas perceived mental health did not change substantially (difference: −0.5 points). Improvement in OHRQoL (difference in OHIP sum score: −6.7 points) was statistically significant. Although the OHIP effect size (of 0.2) was considered as small, according to guidelines, it was greater than for the SF‐36 component scores (physical: 0.1; mental: 0.1). Sensitivity to change in quality of life measures was greater for OHRQoL than for HRQoL, limiting the usefulness of HRQoL as an outcome measure in dentistry.